Optimization of dual-module floating photovoltaic arrays: layout configuration and damping mechanisms for enhanced stability and energy performance - Zheng, Zhi; Hu, Jianjian; Huang, Qiang; Jin, Peng; Yang, Yifeng; Huang, Luofeng; Zhou, Zhaomin; Zhou, Binzhen (Elsevier, 2025)
Floating Photovoltaic (FPV) systems are a promising solution for offshore renewable energy, with modular FPV arrays offering significant potential for large-scale deployment. However, the development of FPV systems is hindered by insufficient understanding of their hydrodynamic performance, which affects stability and energy efficiency. This study proposes a dual-module FPV array combining box-type and semi-submersible modules to improve hydrodynamic stability under mild wave conditions in the South China Sea. The effects of array layout and PTO damping are examined under various wave conditions. The system is optimized to balance energy harvesting and motion control, and its performance is further evaluated under irregular waves at selected operational sites. Results indicate that the dual-module design effectively leverages the hydrodynamic characteristics of both module types, reducing motion responses and dynamic loads. The incorporation of optimal PTO damping further enhances system stability and energy efficiency by effectively suppressing pitch and heave motions, with maximum reductions of 31.43 % and 41.56 %, respectively, under the selected operational wave conditions. While damping remains effective under head-on waves, its performance slightly decreases under oblique waves, underscoring the importance of aligning the array with the predominant wave direction. Additionally, integrating a wave energy PTO system into the FPV array enables wave power to supplement solar energy, contributing 17.04 % of the total energy output at the selected operational sites. The proposed FPV system offers a practical solution for stabilizing floater motion, enhancing solar power generation, and capturing wave energy, advancing the feasibility of FPV technology for large-scale offshore applications.
Keywords: Energy; 4008 Electrical engineering; 4012 Fluid mechanics and thermal engineering; 4017 Mechanical engineering